The Effect of Work-Life Balance on Employee Performance: Evidence from a Four-Star Hotel in Bandung, Indonesia - Sri Marhanah; Eeng Ahman; Syamsul Hadi Senen; Disman Disman (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Work-life balance has become a critical issue in the hospitality industry, which is characterized by high service demands, irregular working hours, and intense work pressure. Despite the growing body of literature on work-life balance and employee performance, empirical evidence focusing on the hospitality sector in Indonesia remains limited. This study aims to examine the effect of work-life balance on employee performance in a four-star hotel in Bandung, Indonesia. A quantitative approach with a descriptive and verificative design was employed. The research population consisted of 50 hotel employees, and a saturated sampling technique was applied. Data were collected using a structured questionnaire with a Likert scale and analyzed through simple linear regression. The results indicate that work-life balance has a positive and significant effect on employee performance, explaining 26.1% of performance variance. This finding suggests that while work-life balance plays an important role in enhancing employee performance, other factors also contribute substantially. The study provides empirical support for the strategic importance of work-life balance policies in service-oriented organizations and offers practical implications for hotel management in improving employee well-being, productivity, and retention. Furthermore, this research contributes to the literature by enriching contextual evidence from the Indonesian hospitality industry and highlighting directions for future research on comprehensive human resource management strategies. Keywords: work-life balance; employee performance; hospitality industry; employee well-being; productivity